Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1677/jme-07-0036
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin targets extracellular signal-regulated kinase signaling pathway in human cancers

Abstract: The mitogen-activated protein kinases (MAPKs) signaling pathway is a potential target in cancer therapy. Constitutive phosphorylated extracellular signal-regulated kinase (ERK1/2), which is one of the MAPKs has been detected in a variety of tumors. Calcitonin (CT) is a polypeptide hormone secreted by the thyroid gland and has been used to treat the osteoporosis and humoral hypercalcemia of malignancy. We report that CT decreases ERK1/2 phosphorylation in cancer cells showing constitutive phosphorylated ERK1/2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…Therefore, we administered calcitonin via subcutaneous route unfortunately without any decrease in serum calcium levels. Glucocorticoids at daily doses of 60 mg can be used in cases refractory to hydration, bisphosphonate, and diuretic therapy (27,28). However, our patient did not respond well to glucocorticoid therapy, either.…”
Section: Discussionmentioning
confidence: 56%
“…Therefore, we administered calcitonin via subcutaneous route unfortunately without any decrease in serum calcium levels. Glucocorticoids at daily doses of 60 mg can be used in cases refractory to hydration, bisphosphonate, and diuretic therapy (27,28). However, our patient did not respond well to glucocorticoid therapy, either.…”
Section: Discussionmentioning
confidence: 56%
“…Previously, we demonstrated that CT activation of LLC-PK1 cells stimulated ERK1/2 phosphorylation through MEK (Nakamura et al, 2002), however, CT suppressed ERK1/2 constitutive activation in human cancer cells (Nakamura et al, 2007). We showed that ERK activation by CT is abolished completely by PD98059, however, CTGF expression induced by CT was a partially inhibited by PD98059.…”
Section: Discussionmentioning
confidence: 69%
“…Total RNA was isolated from each cell line and tissue samples using the ULTRASPEC RNA Isolation System (Biotecx, TX) [18]. cDNA was synthesized using the SuperScript First-Strand Synthesis System for RT-PCR (Invitrogen, CA).…”
Section: Total Rna Isolation Rt-pcr and Detection Of Braf Mutationmentioning
confidence: 99%
“…The PCR reaction primers for uPA and BRAF were as follows: uPA forward 5 -AAGGACTACAGCG-CTGACAC-3 , reverse 5 -AACTCCTGCAGGCTTCAGTC-3 ; BRAF forward 5 -GCACAGGGCATGGATTACTT-3 , reverse 5 -GATGACTTC-TGGTGCCATCC-3 . RT-PCR analysis with ˇ-actin primers was used as an internal quality control [18]. In addition, the purified PCR products of cDNA for the BRAF gene (exon 15) were sequenced using PCR primers as previously described [15].…”
Section: Total Rna Isolation Rt-pcr and Detection Of Braf Mutationmentioning
confidence: 99%